The influence of nutrient solutions on growth, seed production and seed quality of broccoli (Brassica oleracea L. var. italica Plenck) - Du Randt, Marius Louis (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MScAgric (Agronomy))--University of Stellenbosch, 2011.